186k views
15 votes
Determine the solution to the equation below.

2(x-1)= 4x+3

2 Answers

7 votes
-5’2 is the answer to this
User Richard Dingwall
by
6.0k points
2 votes

Answer:

x = -5/2

Explanation:

2(x−1)=4x+3

Step 1: Simplify both sides of the equation.

2(x−1)=4x+3

(2)(x)+(2)(−1)=4x+3(Distribute)

2x+−2=4x+3

2x−2=4x+3

Step 2: Subtract 4x from both sides.

2x−2−4x=4x+3−4x

−2x−2=3

Step 3: Add 2 to both sides.

−2x−2+2=3+2

−2x=5

Step 4: divide all by -2

-2x/ -2 = 5/-2

x = -5/2

User Hossein Piri
by
6.1k points